Biocompatible and Hermetic Encapsulation of PMUTs: Effects of Parylene F-VT4 and ALD Stacks on Membrane Vibration and Acoustic Performance - Esmaeil Afshari; Samer Houri; Rik Verplancke; Veronique Rochus; Maarten Cauwe; Pieter Gijsenbergh; Maaike Op de Beeck (Sensors, 2025)
The motivation of this work is to enable the use of piezoelectric micromachined ultrasonic transducer (PMUT)-based implants within the human body for biomedical applications, particularly for power and data transfer for implanted medical devices. To protect surrounding tissue and ensure PMUT functionality over time, biocompatible and hermetic encapsulation is essential. This study investigates the impact of Parylene F-VT4 layers of various thicknesses as well as the effect of multilayer stacks of Parylene F-VT4 combined with atomic layer-deposited nanolayers of Al2O3 and HfO2 on the mechanical and acoustic properties of PMUTs. PMUTs with various diameters (40 µm, 60 µm, and 80 µm) are fabricated and tested both as stand-alone devices and as arrays. The mechanical behavior of single stand-alone PMUT devices is characterized in air and in water using laser Doppler vibrometry (LDV), while the acoustic output of arrays is evaluated by pressure measurements in water. Experimental results reveal a non-monotonic change in resonance frequency as a function of increasing encapsulation thickness due to the competing effects of added mass and increased stiffness. The performance of PMUT arrays is clearly influenced by the encapsulation. For certain array designs, the encapsulation significantly improved the arrays’ pressure output, a change that is attributed to the change in the acoustic wavelength and inter-element coupling. These findings highlight the impact of encapsulation in modifying and potentially enhancing PMUT performance.